Prostor za dezinstitucionalizacijo - Ficko, Katarina (Socialno delo, 2025)
One of the key issues of deinstitutionalization is often where people will live in the community after resettling from institutions. In the past, in Slovenia, residential group homes have been established as one of the most common (organised) forms of resettlement from institutions. Although initially intended solely as a transitional form or an intermediate step between life in an institution and independent living in the community, experts and users point out that residential groups are not the most suitable way to create living in the community for people returning from institutions, as they often reproduce institutional culture. This raises the question of what types of places are more appropriate and how to create them. The article presents the users’ perspective of residents on an institution, who were involved in the “Dom na Krasu” project and were part of the deinstitutionalization process, and on decision-making regarding the relocation to the community in various ways. Although these individuals were expected to play a key role in the deinstitutionalization process, relocations in the project often occurred without their real participation and without opportunities to decide where, with whom, and how they would live. The article emphasizes that inclusive and suitable spaces for people resettling from institutions are only those that are created together with the users.
Keywords: community; Deinstitucionalizacija; deinstitutionalisation; dezinstitucionalizacija; elocation; inclusion; institucije; institutions; preselitev; residential groups; skupnost; socialnovarstveni zavodi; stanovanjske skupine; vključevanje